Comparative study of wound healing in rat skin following incision with a novel picosecond infrared laser (PIRL) and different surgical modalities. Issue 4 (4th March 2016) - Petersen, Hannes; Tavakoli, Fatemeh; Kruber, Sebastian; Münscher, Adrian; Gliese, Alexandra; Hansen, Nils‐Owe; Uschold, Stephanie; Eggert, Dennis; Robertson, Wesley D.; Gosau, Tobias; Sehner, Susanne; Kwiatkowski, Marcel; et al.
Abstract : Background and Objective: As a result of wound healing the original tissue is replaced by dysfunctional scar tissue. Reduced tissue damage during surgical procedures beneficially affects the size of the resulting scar and overall healing time. Thus the choice of a particular surgical instrument can have a significant influence on the postoperative wound healing. To overcome these problems of wound healing we applied a novel picosecond infrared laser (PIRL) system to surgical incisions. Previous studies indicated that negligible thermal, acoustic, or ionization stress effects to the surrounding tissue results in a superior wound healing. Study Design/Materials and Methods: Using the PIRL system as a surgical scalpel, we performed a prospective wound healing study on rat skin and assessed its final impact on scar formation compared to the electrosurgical device and cold steel. As for the incisions, 6 full‐thickness, 1‐cm long‐linear skin wounds were created on the dorsum of four rats using the PIRL, an electrosurgical device, and a conventional surgical scalpel, respectively. Rats were euthanized after 21 days of wound healing. The thickness of the subepithelial fibrosis, the depth and the transverse section of the total scar area of each wound were analyzed histologically. Results: After 21 days of wound healing the incisions made by PIRL showed minor scar tissue formation as compared to the electrosurgical device and the scalpel. Highly significant differences ( P < 0.001) were noted by comparing the electrosurgical device with PIRL and scalpel. The transverse section of the scar area also showed significant differences ( P = 0.043) when comparing PIRL (mean: 141.46 mm 2 ; 95%CI: 105.8–189.0 mm 2 ) with scalpel incisions (mean: 206.82 mm 2 ; 95%CI: 154.8–276.32 mm 2 ). The subepithelial width of the scars that resulted from using the scalpel were 1.3 times larger than those obtained by using the PIRL (95%CI: 1.0–1.6) though the difference was not significant ( P < 0.083). Conclusions: The hypothesis that PIRL results in minimal scar formation with improved cosmetic outcomes was positively verified. In particular the resection of skin tumors or pathological scars, such as hypertrophic scars or keloids, are promising future fields of PIRL application. Lasers Surg. Med. 48:385–391, 2016. © 2016 Wiley Periodicals, Inc.